The oasis system in southern Algeria: a natural heritage threatened with disappearance, case of the oasis of Biskra - Berbache, Hadjira; Khaoui, Mohamed; Hadjab, Makhloufi (Technium Social Sciences Journal, 2022)
The objective of the study presented in this paper is to monitor the urban transformation witnessed by the Biskra Oasis, by addressing its various characteristics, manifestations and negative effects on the natural heritage. In this study, we relied geographically on field sampling that is based on the descriptive analytical approach, in addition to the historical approach to highlight the spatial development of the study area. The study showed that the oasis of Biskra became living in a disturbing environmental situation, to the extent that some people sounded the alarm to draw attention to the slow death experienced by this oasis area, which began to know a new reality due to the urban transformation. In addition, the study concluded the disappearance of a many number of palm groves, The study also revealed the loss of the identity of the oasis, the quality of its landscapes, and the tourist value. This situation finds its explanation in the various imbalances in the ecological balances that were ensuring the continuity of the oasis. This is the main proposal to make an accurate diagnosis of the environmental reality in order to foresee a balanced environment and to identify the mechanisms and methods of preserving the oasis